A pumpless multi‐organ‐on‐a‐chip (MOC) combined with a pharmacokinetic–pharmacodynamic (PK–PD) model. Issue 2 (14th September 2016) - Lee, Hyuna; Kim, Dae Shik; Ha, Sang Keun; Choi, Inwook; Lee, Jong Min; Sung, Jong Hwan
ABSTRACT: A multi‐organ‐on‐a‐chip (MOC), also known as a human‐on‐a‐chip, aims to simulate whole body response to drugs by connecting microscale cell cultures of multiple tissue types via fluidic channels and reproducing the interaction between them. While several studies have demonstrated the usefulness of MOC at a proof‐of‐concept level, improvements are needed to enable wider acceptance of such systems; ease of use for general biological researchers, and a mathematical framework to design and interpret the MOC systems. Here, we introduce a pumpless, user‐friendly MOC which can be easily assembled and operated, and demonstrate the use of a PK–PD model for interpreting drug's action inside the MOC. The metabolism‐dependent anticancer activity of a flavonoid, luteolin, was evaluated in a two‐compartment MOC containing the liver (HepG2) and the tumor (HeLa) cells, and the observed anticancer activity was significantly weaker than that anticipated from a well plate study. Simulation of a PK–PD model revealed that simultaneous metabolism and tumor‐killing actions likely resulted in a decreased anti‐cancer effect. Our work demonstrates that the combined platform of mathematical PK–PD model and an experimental MOC can be a useful tool for gaining an insight into the mechanism of action of drugs with interactions between multiple organs. Biotechnol. Bioeng. 2017;114: 432–443. © 2016 Wiley Periodicals, Inc. Abstract : Multi‐organ‐on‐a‐chip recapitulates simultaneous metabolism and cell‐killing effect of drugs, and its action inside the chip is simulated with a PK–PD model, providing insight into the action of the drug.